2012
DOI: 10.1111/j.1461-0248.2011.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Intralocus sexual conflict and offspring sex ratio

Abstract: Males and females frequently have different fitness optima for shared traits, and as a result, genotypes that are high fitness as males are low fitness as females, and vice versa. When this occurs, biasing of offspring sex-ratio to reduce the production of the lower-fitness sex would be advantageous, so that for example, broods produced by high-fitness females should contain fewer sons. We tested for offspring sex-ratio biasing consistent with these predictions in broad-horned flour beetles. We found that in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…This protocol ensures that the emerging adults do not interact with conspecifics. As G. cornutus males can take up to 7 days to attain sexual maturity ( [45] and see [36]), we allowed individuals from both sexes to mature for 14 days before being used in experiments. All experiments within this study follow this maintenance protocol, unless stated otherwise.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This protocol ensures that the emerging adults do not interact with conspecifics. As G. cornutus males can take up to 7 days to attain sexual maturity ( [45] and see [36]), we allowed individuals from both sexes to mature for 14 days before being used in experiments. All experiments within this study follow this maintenance protocol, unless stated otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…Lifetime reproductive success (LRS) of each female was scored as the total number of adult offspring emerging from these vials. This provides a good proxy for female LRS (see [36,45,59]), and such proxies of LRS have been used to good effect in other studies [60]. Females were then moved into new vials (40 mm high, 15 mm diameter) containing an excess of the culture medium (4 g) and assessed for survival weekly until death.…”
Section: (A) Direct Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain environmental conditions, it may be beneficial to produce mainly males and in alternative environments it may be beneficial to produce mainly females, 3 causing sexual antagonism for offspring gender. The ability of mammalian mothers to adjust the sex ratio of their offspring is poorly understood although empirical and theoretical studies in other species have shown that: (i) it is possible; 4 and (ii) it is adaptive. 2 Little is known, however, whether humans are able to manipulate the sex ratio of offspring to maximize their reproductive success and that of their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…So far, it is well recognised that many factors, such as LMC (Hamilton, 1967), resource competition (Clark, 1978), maternal quality (Trivers & Willard, 1973), mate attractiveness (Burley, 1981) and variable environment (Charnov, Los-den Hartogh, Jones, & van den Assem, 1981), affect how a mother adjusts her progeny's sex ratios to maximise the fitness returns (House, Simmons, Kotiaho, Tomkins, & Hunt, 2011). Recently, there have been several empirical studies on the sex allocation of beetles examining the above factors (Cruickshank & Wade, 2012;House et al, 2011;Katsuki, Harano, Miyatake, Okada, & Hosken, 2012;Keller, Peer, Bernasconi, Taborsky, & Shuker, 2011;Figure 2. Percentage of female progeny (a) and the rate of population increase (b) for A. hygrophila under different adult sex ratios.…”
Section: Discussionmentioning
confidence: 98%